My top 20 weird animals - Parker, Steve (United Kingdom : Miles Kelly, 2010)
What could a male Jackson's chameleon need three horns for besides fighting? Actually, this odd-looking animal has horns to scare predators and attract females more than defense. Some animals' bodies can lead readers to question the purpose of their weird features. This book has the answers they're looking for. From how the echidna uses its spines to keep predators away to how the hornbill uses its large beak, the main content features some of nature's most interesting bodies. Colorful, up-close photographs and concise fact boxes introduce readers to many kinds of animal habitats, behaviors, and life cycles.
Keywords: Animals -- Education -- Nature -- ANIMAL FOCUS